Pendidikan Berkelanjutan dan Berwawasan Lingkungan sebagai Arah Baru Pendidikan Indonesia - I Wayan Karmana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Sustainable and environmentally conscious education is one of the strategic directions of Indonesian education in responding to global challenges, particularly the environmental crisis and the demands of sustainable development. This article aims to systematically examine the development of the concept, implementation, and challenges of sustainable education as a new direction for Indonesian education. This study uses the Systematic Literature Review (SLR) method, by analyzing 15 national and international scientific articles published within the last five years. The literature search was conducted through Google Scholar, Scopus, and DOAJ databases, with predetermined inclusion criteria. The results of the study indicate that sustainable education is understood as a holistic approach that integrates ecological, social, and economic dimensions in the learning process, and emphasizes the formation of pro-environmental attitudes and behaviors of students. The implementation of sustainable education in Indonesia has been pursued through national policies, particularly the Independent Curriculum, the Pancasila Student Profile Strengthening Project, and the environmentally conscious school program. However, its implementation remains uneven and faces challenges such as limited educator competency, incomplete curriculum integration, and varying institutional support. This study concludes that sustainable and environmentally conscious education needs to be positioned as the basic framework for developing the national education system to achieve quality, competitiveness, and environmental responsibility.